Tissue partition and risk assessments of trace elements in Indo-Pacific Finless Porpoises (Neophocaena phocaenoides) from the Pearl River Estuary coast, China. (October 2017) - Zhang, Xiyang; Lin, Wenzhi; Yu, Ri-Qing; Sun, Xian; Ding, Yulong; Chen, Hailiang; Chen, Xi; Wu, Yuping
Abstract: Throughout the last few decades, an increased number of stranded marine mammals, particularly the Indo-Pacific Finless Porpoises ( Neophocaena phocaenoides ), were observed in the Pearl River Estuary (PRE). As long-lived, apex predators vulnerable to bioaccumulation of contaminants, the tissue residue levels and health risk of trace elements (TEs) in N. phocaenoides from the PRE have been little studied. Eleven typical TEs distributed in skin, liver and kidney tissues were investigated from 25 specimens stranded along the PRE from 2007 to 2015 in the present study. It revealed that most TEs were highly accumulated in internal organs (liver and kidney), except for Zn with high residue levels in external skin. Compared with the TEs in prey items, the residue levels of Hg, Se, Zn, Cu, Cd and Cr in N. phocaenoides increased 4-618 times, indicating a potentially significant biomagnification. Sex-related differences of TE accumulation were not obvious, except for renal Mn, in which the females showed lower mean concentrations than males. Significantly positive correlations between body length and TE levels were found for Hg, Se and Cd. Results of the calculated risk quotients (RQ) suggested that the risks to N. phocaenoides from consumption of prey items were generally low, but further attentions should be paid to Cd, Cr, Cu, Hg and As due to the elevated RQ values. The concentrations of Hg, Cd and Se in the epidermis were positively correlated with the levels found in internal organs. Our investigation provides evidence to support the use of skin as one biomonitoring approach on Hg, Cd and Se contamination of internal tissues in this species. Graphical abstract: Highlights: Hg, Se and Cd showed highest residue levels in liver and strong correlations with body length. Significant biomagnification of trace elements occurred in N. phocaenoides. Heavy metal risks to N. phocaenoides from prey item consumption were generally low. Our results support the use of skin to evaluate Hg, Cd and Se levels in internal organs of N. phocaenoides .